2020
DOI: 10.1200/cci.20.00008
|View full text |Cite
|
Sign up to set email alerts
|

Prior Treatment Time Affects Survival Outcomes in Metastatic Breast Cancer

Abstract: PURPOSE Sequential drug treatments in metastatic breast cancer (MBC) are disparate. Clinical trial data includes limited reporting of treatment context, primarily including the number of prior therapies. This study evaluates the relationship between prior treatment time, prior lines of treatment, and survival using a novel visualization technique coupled with statistical analyses. PATIENTS AND METHODS This retrospective cohort study used a nationwide, de-identified electronic health record–derived database to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…[15][16][17] The early disease may be the most adequate setting to evaluate the real impact of beta-blockers on patients with breast cancer, since patient outcomes in this scenario are not influenced by potential subsequent lines of treatment, as it occurs in those with advanced disease. 18,19 In this regard, we carried out a systematic review and meta-analysis to assess the impact of beta-blockers on the outcomes of patients with early-stage breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The early disease may be the most adequate setting to evaluate the real impact of beta-blockers on patients with breast cancer, since patient outcomes in this scenario are not influenced by potential subsequent lines of treatment, as it occurs in those with advanced disease. 18,19 In this regard, we carried out a systematic review and meta-analysis to assess the impact of beta-blockers on the outcomes of patients with early-stage breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A study evaluating patients receiving Palbociclib and Letrozole demonstrated that patients without prior cancer treatments who received this regimen had a two-fold PFS benefit compared to those with prior endocrine therapy or chemotherapy [ 14 ]. Similarly, an analysis of patients with MBC receiving paclitaxel, where patients experienced an increased hazard of death of 71% with one line of treatment before paclitaxel, a 30% increase with two prior treatments, and a 123% increase with three or more prior treatments compared to those with no prior treatments before paclitaxel [ 15 ]. Together these studies emphasize the importance of considering both duration and type of prior therapy when interpreting clinical trials results.…”
Section: Discussionmentioning
confidence: 99%
“…Given the challenge in capturing these higher dimensional data for different treatment sequences and their metadata, we employed our visualization algorithm to help create a topological representation of such heterogeneity [ 15 , 18 ]. The features of the resultant treatment sequence graph can inform us about sequence frequency, median survival, overall average prior lines, and performance of any specific agent on disease behavior and outcome within the large sequence landscape of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Metastasis and tumor recurrence, which significantly impair treatment, are the major causes of poor outcome. 7 Therefore, identifying novel and effective treatment strategies for preventing and treating breast cancer is an active area of research.…”
Section: Introductionmentioning
confidence: 99%